This is also a prison, although more in a therapeutic sense: practices, discourses and thoughts from the prison world in regards to the SPF psychiatric services - Natalia Lombraña, Andrea (2017)
The progressive system is the mode of execution of the prison sentence used in Argentina, through which it seeks to promote the “social reinsertion” of prison system inmates   (since   the   constitutional   criminal justice system reform in 1994). This is the central axis on which the institutional dynamics of the Federal Prison Service is structured, both as regards the spatiotemporal organisation of prisoners and workers, and also the relations between them inside the contemporary prison in the country. However, the national law enforcement regulatory process decided that all persons held permanently or temporarily in psychiatric prisons are excluded from this system. The article analyses some of the negative implications this exclusion has on both the development of prisons and the spaces destined for the treatment of mental health in federal prisons. This is based on data obtained in the development of an anthropological project (2010-2014) carried out